ESOMAT 2009 - 8th European Symposium on Martensitic Transformations 2009
DOI: 10.1051/esomat/200901003
|View full text |Cite
|
Sign up to set email alerts
|

Development of high temperature Ti-Ta shape memory alloys

Abstract: Abstract. Recent development of Ti-Ta and Ti-Ta-Al high temperature shape memory alloys was reviewed. The effect of Ta content on shape memory behavior of Ti-Ta alloys was first described. Shape memory effect was confirmed in Ti-(30-40)Ta alloys. The Ms formed during aging decreased with increasing Ta so that stable high temperature shape memory effect was confirmed for Ti-32Ta (Ms=440K) during thermal cycling between 173K and 513K. Secondly, the effect of ternary alloying elements (X = V, Cr, Fe, Zr, Hf, Mo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…In fact, due to the very weak β stabilizing effect, Zr is often referred to as being a neutral stabilizer . However, it has been experimentally found that high concentrations of Nb and Ta can convert Zr (and Hf) into a strong β stabilizer . Based on the picture of the electronic interactions in Ti and Ti alloys developed here, we tentatively attribute this behavior to the excess electrons from the Nb/Ta solutes that assist in further strengthening the Ti–Zr bonds in β Ti.…”
Section: Resultsmentioning
confidence: 65%
“…In fact, due to the very weak β stabilizing effect, Zr is often referred to as being a neutral stabilizer . However, it has been experimentally found that high concentrations of Nb and Ta can convert Zr (and Hf) into a strong β stabilizer . Based on the picture of the electronic interactions in Ti and Ti alloys developed here, we tentatively attribute this behavior to the excess electrons from the Nb/Ta solutes that assist in further strengthening the Ti–Zr bonds in β Ti.…”
Section: Resultsmentioning
confidence: 65%
“…Ta-Ti alloys have been proposed as one of the best choices for biomedical applications based on their excellent biocompatibility in the human body environment, high strength, relatively low elastic moduli and enhanced corrosion resistance [1,2,3,4,5,6]. These alloys are also attractive for applications in advanced actuators since they exhibit shape memory behavior at relatively high temperatures due to a reversible martensitic transformation between the meta-stable bcc phase and the α" martensite phase [7,8,9,10,11,12,13]. Despite the potential applications of these alloys, important gaps exist in our knowledge of their binary phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…At these temperatures, martensitic transformation is observed in Zr-based alloys (ZrCo, ZrCu, ZrCuCo, ZrCuNi, ZrCоNi, ZrRh), HfIr, ТiTa [42][43][44]. For example, in alloy Zr 2 CоNi, direct martensitic transformation is beginning at 600С during cooling, and reverse transformation under heating is finished at 900С; martensitic transition is characterized by wide temperature hysteresis.…”
Section: 2mentioning
confidence: 99%